Study on the infectious capacity of feed experimentally contaminated with influenza A virus (Romanian Biotechnological Letters, 2025)
Influenza A virus (IAV) is mainly transmitted from one to another host through excretions and secretions in the form of droplets and aerosols. It is also possible that the virus is transmitted indirectly through a contaminated environment. The likelihood of transmission through the environment depends on several factors, including the survival time of the virus in secretions/excretions on contaminated surfaces, including feed. However, the transmission of IAV through feed has not been sufficiently investigated. In this study, the half-life of the IAV virus at the level of nucleic acid in feed was compared under certain conditions. Different concentrations of IAV subtype H3N2 (100 to 106 EID50) were applied to feed samples from a broiler breeding farm, which were then heat treated at -20, 4, 25 and 37°C, for 24, 48 and 72h. The IAV concentration in all samples was measured by determining RNA for the matrix protein by RT-qPCR and the half-life of the virus was calculated. The half-life of the virus in the feed samples was compared with that of the Brain Hart Infusion (BHI) protective medium, used as a control. The half-lives identified for feed and BHI environment were 19 h and 41 h respectively for 37°C, and 56 h for BHI at 25°C. The half-lives for the other temperatures were insignificant for the two matrices. The half-life was longer for the feed compared to the BHI medium at temperatures above 25°C. The viral titre had a sharp drop at temperature of 37°C with a steeper slope in the case of the BHI environment compared to the feed. The evaluation of the infectivity of the virus remaining in the two matrices by inoculating suspensions on embryonated eggs highlighted the fact that the feed does not allow the viability of the virus to be preserved even in the case of testing immediately after inoculation. Therefore, the transmission of IAV subtype H3N2 may not play a significant role in the spread of the virus.
Keywords: influenza virus type A; feed; polymerase chain reaction; half-life